2020
DOI: 10.1016/j.neuron.2020.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Neuronal Diversity during Vertebrate Brain Development

Abstract: Neurogenesis in the vertebrate brain comprises many steps ranging from the proliferation of progenitors to the differentiation and maturation of neurons. Although these processes are highly regulated, the landscape of transcriptional changes and progenitor identities underlying brain development are poorly characterized. Here, we describe the first developmental single-cell RNAseq catalog of more than 200,000 zebrafish brain cells encompassing 12 stages from 12 hours post-fertilization to 15 days post-fertiliz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 86 publications
(88 reference statements)
5
68
0
Order By: Relevance
“…These post-embryonic RPCs possess the capacity to generate clones of both size and composition comparable to embryonic RPCs ( Wan et al, 2016 ). Correspondingly, embryonic and post-embryonic zebrafish RPCs display similar gene expression profiles when examined at single-cell resolution ( Raj et al, 2020 ; Xu et al, 2020 ). Though mice lack the innate ability to undergo retinal regeneration or continuously generate new neurons throughout the lifespan of the animal, studies have demonstrated that Msx1 + progenitor cells derived from the proximal zone of mouse CMZ give rise to both RPCs and non-neural epithelia during embryonic periods of development ( Bélanger et al, 2017 ; Marcucci et al, 2016 ).…”
Section: Retinal Progenitor Cells—the Evolving Transcriptome Of Rpcs Across Developmentmentioning
confidence: 94%
See 4 more Smart Citations
“…These post-embryonic RPCs possess the capacity to generate clones of both size and composition comparable to embryonic RPCs ( Wan et al, 2016 ). Correspondingly, embryonic and post-embryonic zebrafish RPCs display similar gene expression profiles when examined at single-cell resolution ( Raj et al, 2020 ; Xu et al, 2020 ). Though mice lack the innate ability to undergo retinal regeneration or continuously generate new neurons throughout the lifespan of the animal, studies have demonstrated that Msx1 + progenitor cells derived from the proximal zone of mouse CMZ give rise to both RPCs and non-neural epithelia during embryonic periods of development ( Bélanger et al, 2017 ; Marcucci et al, 2016 ).…”
Section: Retinal Progenitor Cells—the Evolving Transcriptome Of Rpcs Across Developmentmentioning
confidence: 94%
“…In order to better appreciate the mechanisms governing temporal cell fate specification, researchers have recently employed large-scale scRNA-seq to profile the in vivo development of retinas in mice, humans, chicken, and zebrafish as well as the in vitro generation of human ES-cell/iPS-cell derived retinal organoids ( Clark et al, 2019 ; Collin et al, 2019 ; Cowan et al, 2020 ; Hu et al, 2019 ; Lu et al, 2020 ; Raj et al, 2020 ; Sridhar et al, 2020 ; Xu et al, 2020 ; Yamagata et al, 2021 ). These scRNA-seq studies have answered many questions regarding RPC heterogeneity at individual ages and across development, but have yet to definitively assign competence transitions within the developing vertebrate retina.…”
Section: Retinal Progenitor Cells—the Evolving Transcriptome Of Rpcs Across Developmentmentioning
confidence: 99%
See 3 more Smart Citations